Forms of Integrated Marketing Communications For Community Products by the Locals of Good Agriculture Practice –Klongha Sub-district, Klongluang District, Pathum Thani, Thailand - et. al., Wareerat Sampatpong, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research of the forms of integrated marketing communications for community products by the group of a good agriculture practice aimed to study the various forms of marketing communication through participated process with the deep interview, group discussion, and participated observation. The 30 informants were selected from five groups of the community leaders, the good agricultural practice group, the housewives, the teenagers, and the seniors. The result showed that the old forms of advertisements such as wording, brochures, community banners have been made while the channels via social medias were added to increase the product selling to focus on the specific customer groups. Moreover, the product-booth show has also been supported and publicized by the state. The community has intended to produce the varieties of products and to advertise through different marketing tools, both online and offline, focusing on the public activities. The uniqueness and characteristics of the good agricultural products have continuously been improved to acknowledge the products widely. Based on the research information, the paradigm of marketing communication forms for the mentioned products has been called ‘ The SPECIAL Paradigm’ with the researcher’s intention that the entrepreneurs can form the ideal frame for integrated marketing communication in the future.